Exploring a Synergistic Approach: Dual GLP-1 Agonist Combined with Degludec Basal Insulin for Early Type 1 Diabetes Treatment and its Impact on Albumin-Insulin Producing Cells Expression - Amr Ahmed; Maher Monir. Akl (Advanced Pharmaceutical Bulletin)
Purpose: This manuscript explores the potential of dual glucagon-like peptide 1 (GLP-1) agonists combined with degludec basal insulin as a treatment approach for early type 1 diabetes. The study aims to evaluate the efficacy and mechanistic impact of semaglutide, a GLP-1 agonist, on newly diagnosed type 1 diabetes patients. Methods: A retrospective analysis was conducted to assess the effects of semaglutide on individuals with early type 1 diabetes. The analysis focused on the elimination of prandial and basal insulin, changes in C-peptide levels, and overall glycemic control. The study also examined the potential for GLP-1 agonists to protect residual beta cells, stimulate cell proliferation, and reprogram liver cells into insulin-producing cells. Additionally, the modification of GLP-1 agonists with albumin ligands to extend their half-life and enhance their anti-diabetic effects was investigated. Results: The findings demonstrate the elimination of both prandial and basal insulin requirements, an increase in C-peptide levels, and improved glycemic control among the patients. Despite the positive outcomes, the study’s retrospective nature and absence of a control group highlight the necessity for larger, prospective trials. Conclusion: GLP-1 agonists show considerable potential in the management of type 1 diabetes by protecting residual beta cells, promoting cell proliferation, and reprogramming hepatic cells. The integration of modified GLP-1 agonists with albumin ligands could further enhance these effects. The manuscript underscores the need for continued research to fully explore this therapeutic approach. The proposed treatment strategy, which combines the autoimmune hypothesis, the proliferative effects of GLP-1, and albumin ligand modifications, aims to restore beta cell mass and function, thereby improving the quality of life for individuals with type 1 diabetes. Clinical trials are planned for 2024 under the registration ‹Amr Ahmed, Maher M. Akl, Semaglutide GLP1 Agonists with Degludec Basal-bolus Insulin in Early Type 1 Diabetes to Basalbolus› (ClinicalTrials.gov Identifier NCT06057077).